Hubungan Ekspor, Kurs Rupiah, Dan Inflasi Terhadap Cadangan Devisa Indonesia - sitorus, Elfrida br; Nopeline, Nancy; Purba, Elvis F (JOURNAL ECONOMICS AND STRATEGY, 2025)
This study aims to analyze the effect of export volume, rupiah exchange rate, and inflation on Indonesia’s foreign exchange reserves during the period 2000–2023. The data used are secondary data obtained from the Central Bureau of Statistics (BPS) and Bank Indonesia (BI). The analysis was conducted using multiple linear regression with the EViews 12 software. The results show that export volume and the rupiah exchange rate have a positive and significant effect on foreign exchange reserves, while inflation has a negative and significant effect. The coefficient of determination (R²) of 0.9462 indicates that the three independent variables explain 94.62% of the variation in Indonesia’s foreign exchange reserves, while the remainder is influenced by other factors outside the model. These findings highlight that increasing exports and maintaining exchange rate stability strengthen foreign exchange reserves, whereas high inflation weakens them. Therefore, controlling inflation and enhancing exports are crucial strategies for sustaining Indonesia’s foreign exchange reserve stability.